Molecular microbial diversity of an anaerobic digestor as determined by small-subunit rDNA sequence analysis. - Godon, J J (1997)
The bacterial community structure of a fluidized-bed reactor fed by vinasses (wine distillation waste) was analyzed. After PCR amplification, four small-subunit (SSU) rDNA clone libraries of Bacteria, Archaea, Procarya, and Eucarya populations were established. The community structure was determined by operational taxonomic unit (OTU) phylogenetic analyses of 579 partial rDNA sequences (about 500 bp long). A total of 146 OTUs were found, comprising 133, 6, and 7 from the Bacteria, Archaea, and Eucarya domains, respectively. A total of 117 bacterial OTU were affiliated with major phyla: low-G+C gram-positive bacteria, Cytophaga-Flexibacter-Bacteroides, Proteobacteria, high-G+C gram-positive bacteria, and Spirochaetes, where the clone distribution was 34, 26, 17, 6, and 4%, respectively. The other 16 bacterial OTUs represent 13% of the clones. They were either affiliated with narrow phyla such as Planctomyces-Chlamydia, green nonsulfur bacteria, or Synergistes, or deeply branched on the phylogenetic tree. A large number of bacterial OTUs are not closely related to any other hitherto determined sequences. The most frequent bacterial OTUs represents less than 5% of the total bacterial SSU rDNA sequences. However, the 20 more frequent bacterial OTUs describe at least 50% of these sequences. Three of the six Archaea OTUs correspond to 95% of the Archaea population and are very similar to already known methanogenic species: Methanosarcina barkeri, Methanosarcina frisius, and Methanobacterium formicicum. In contrast, the three other Archaea OTUs are unusual and are related to thermophilic microorganisms such as Crenarchaea or Thermoplasma spp. Five percent of the sequences analyzed were chimeras and were removed from the analysis.